ANALISIS MINAT SISWA DALAM MENGGUNAKAN INSTAGRAM SEBAGAI SUMBER MEDIA PEMBELAJARAN MATEMATIKA - Fauza, M.Ruskhan; In’am, Akhsanul; Effendi, Mohammad Mahfud; Lony, Adrina (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
The purpose of this study was to determine students' interest in social media Instagram as a source of mathematics learning media. This research uses descriptive qualitative research. The subjects in this study were 10 people consisting of various levels and schools in the 2021/2022 academic year and research was carried out at the researcher's home. The main research instrument is the researcher himself and the supporting instruments are observations, questionnaires and interviews. The results of this study prove that students have an interest in learning mathematics using Instagram media. It is proven that student interest consists of 4 aspects, namely aspects of feeling happy, student interest, student attention, and student involvement. Each aspect has a high average, namely: 1) the aspect of feeling happy with an average result of 68.75%, 2) the aspect of student interest with an average result of 70.31%, 3) the aspect of student attention with an average result 67.5%, and 4) aspects of student involvement with an average result of 67.5%. From these data, it proves that students are interested in learning mathematics using Instagram media.